A Hierarchical Core-Shell Structure of NiO@Cu2O-CF for Effective Non-Enzymatic Electrochemical Glucose Detection - Yueyun Huang; Jiahua You; Yingru Ding; Yun Xie; Ting Wang; Fanglong Zhu; Weiping Gong; Zhenting Zhao (Nanomaterials)
Non-enzymatic glucose detection is an effective strategy to control the blood glucose level of diabetic patients. A novel hierarchical core–shell structure of nickel hydroxide shell coated copper hydroxide core based on copper foam (Ni(OH)2@Cu(OH)2-CF) was fabricated and derived from NiO@Cu2O-CF for glucose sensing. Cyclic voltammetry and amperometry experiments have demonstrated the efficient electrochemical catalysis of glucose under alkaline conditions. The measurement displays that the fabricated sensor exhibits a detection scale of 0.005–4.5 mM with a detection sensitivity of 4.67 µA/µM/cm2. It has remarkable response/recovery times in respect of 750 μM glucose (1.0 s/3.5 s). Moreover, the NiO@Cu2O-CF shows significant selectivity, reliable reproducibility and long-term stability for glucose determination, suggesting it is a suitable candidate for further applications.